Legal Protection for Doctors Providing Health Services: A Study of Decision Number 365 K/Pid/2012 - Rudi Mahruzar; Marice Simarmata; Muhammad Arif Sahlepi (Jurnal Multidisiplin Indonesia, 2026)
Legal protection for doctors in the provision of health care services remains an important issue within the Indonesian legal system. This study analyzes the application of the principle of lex posterior derogat legi priori in Supreme Court Decision Number 365 K/Pid/2012 as well as the legal protection afforded to doctors. Objectives: a. To determine how the principle of lex posterior derogat legi priori is applied in the case of Supreme Court Decision Number 365 K/Pid/2012. b. To determine how legal protection is provided to doctors who deliver medical services to patients. The method used is normative juridical research with a statutory approach, a conceptual approach, and a case study of Supreme Court Decision Number 365 K/Pid/2012. Results: In Supreme Court Decision Number 365 K/Pid/2012, a normative conflict occurred between the Criminal Code (KUHP) as general criminal law and the Medical Practice Law as a newer and more specific law. The judicial review decision that acquitted the defendant reflects the application of the principle of lex posterior derogat legi priori as well as the positioning of criminal law as ultimum remedium. In the context of current positive law, the enactment of Law Number 17 of 2023 on Health and Criminal Code Number 1 of 2023 further strengthens legal protection for doctors who carry out their practice in accordance with professional standards and operational procedures. 1. Supreme Court Decision Number 365 K/Pid/2012 demonstrates the application of the principle of lex posterior derogat legi priori. 2. The importance of legal protection for doctors